PERCEIVED EFFECTIVENESS OF EXTENSION SERVICE DELIVERY UNDER INSURGENCY AMONG WHEAT PRODUCING FARMERS IN SOUTHERN BORNO, BORNO STATE, NIGERIA - Wakil, H. A.; Idi, S.; Atman, F. M.; Garba, M.; Dabo, N. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the perceived effectiveness of extension service delivery under insurgency among wheat-producing farmers in Southern Borno, Nigeria. A multistage sampling technique was used to select 322 wheat farmers from Bayo and Biu LGAs. Data were collected using structured questionnaires and analyzed using descriptive statistics and logistic regression. Results revealed that respondents were predominantly middle-aged (mean = 43 years), had an average household size of 9 persons, and mostly operated on small farm sizes (0.5–1.0ha). The most widely disseminated technologies included improved seed varieties (84.9%), fertilizer application (84.9%), and pest and disease control practices (84.9%). Farmers rated improved seed varieties, fertilizer use, pest control, and post-harvest handling as effective, while modern irrigation techniques were perceived as not effective. Logistic regression results showed that sex, marital status, cooperative membership, years of membership, frequency of extension contact, access to credit, and method of land acquisition significantly influenced access to extension services (P< 0.05). The study concludes that while extension services remain relevant and moderately effective, insurgency has severely constrained mobility, frequency of contact, and technology dissemination. Strengthening extension delivery mechanisms, particularly through cooperatives, ICT tools, and enhanced security support, is recommended to improve resilience and wheat productivity in conflict-affected regions.